Proyecto de factibilidad para la creación de una empresa que ofrecerá servicios de aromaterapia e hidroterapia, ubicada en la ciudad de Zamora, provincia de Zamora Chinchipe - Ortiz Maca, Iveth Esperanza (2013)
The objective this research work is to determine the feasibility of launching a company that will offer aromatherapy and hydrotherapy services located in the city of Zamora, this research includes the analysis and development of market study, marketing analysis, technical study, financial study and financial evaluation. In the development of market study will be seen, after the survey sheet application that the market in services sector especially the area of alternative therapies is not yet fully exploited, the results show a high acceptance for new companies invest in the environment and can meet the tastes and preferences of consumers regarding application techniques and quality of alternative therapies services being well social goal of project.